2016
DOI: 10.1002/adfm.201504964
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Crystallization‐Driven Assembly of Conjugated Polymers/Quantum Dots into Coaxial Hybrid Nanowires: Elucidation of Conjugated Polymer Arrangements by Electron Tomography

Abstract: A simple and practical “solution‐biphase method” allows the preparation of efficient charge‐transporting 1D nanocrystals with coaxial p–n junctions. It involves gradual diffusion of a top layer of poor solvent (acetonitrile) into a bottom layer of poly(3‐hexyl thiophene)‐b‐poly(2‐vinyl pyridine) (P3HT‐b‐P2VP) conjugated polymers (CPs) and CdSe quantum dots (QDs) dissolved in chloroform. Initial interfacial crystallization‐driven assembly of CPs results in the formation of seeds consisting of dimeric QDs transv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…The resulting nanostructures show colloidal stability due to the presence of the solvent swollen corona and have been exploited for a variety of uses including the delivery of therapeutic cargoes in nanomedicine 2 , as additives for friction reduction 3 , fillers for composite reinforcement 4 or for the formation of nanoscopic arrays using optical tweezers 5 . However, although recent advances have described examples of fibre-like micelles with novel photophysical characteristics 6 7 , their assembly into complex semiconducting particles, bundles and branched superstructures 8 9 10 11 , and their fabrication of coaxial nanowires with quantum dots 12 13 , ordered two-dimensional assemblies at interfaces 14 and solar cells 15 , the evaluation of their potential as functional electroactive materials in devices is virtually unexplored 14 15 ; specifically, uniform samples of low length dispersity have not been investigated.…”
mentioning
confidence: 99%
“…The resulting nanostructures show colloidal stability due to the presence of the solvent swollen corona and have been exploited for a variety of uses including the delivery of therapeutic cargoes in nanomedicine 2 , as additives for friction reduction 3 , fillers for composite reinforcement 4 or for the formation of nanoscopic arrays using optical tweezers 5 . However, although recent advances have described examples of fibre-like micelles with novel photophysical characteristics 6 7 , their assembly into complex semiconducting particles, bundles and branched superstructures 8 9 10 11 , and their fabrication of coaxial nanowires with quantum dots 12 13 , ordered two-dimensional assemblies at interfaces 14 and solar cells 15 , the evaluation of their potential as functional electroactive materials in devices is virtually unexplored 14 15 ; specifically, uniform samples of low length dispersity have not been investigated.…”
mentioning
confidence: 99%
“…N-type quantum dots or fullerenes and p-type P3HT-containing BCPs have been used to form hybrid nanowires by solution processing routes. [256][257][258] 6.5 Applications of BCP micelles for lubrication and composite reinforcement, and as stabilizers.…”
Section: Etch Resists In Nanolithography and Functional Nanostructurementioning
confidence: 99%
“…During the dip-coating process, the solvent properties of the top phase solution strongly affected the resulting lm formation as well as the crystallization behavior of the conjugated polymer. 27,28 The solvent evaporation rate is one of the most critical factors controlling the crystallinity of a polymer lm prepared by dip coating. A high boiling point solvent can facilitate crystallization among polymer chains by prolonging the solvent evaporation time.…”
Section: The Secondary Solvent Addition Processmentioning
confidence: 99%
“…Numerous studies have reported that solvent additive-assisted solution processes can perform better than systems prepared without a solvent additive. 27,34,35 We tested solvent additives in the biphasic dip-coating method in two different ways ( Fig. 2b): (1) by oating the solvent additive on a polymer-dissolving top-phase solution (oating method); and (2) by mixing the solvent additive with the polymerdissolving solution before forming a biphasic system (mixing method).…”
Section: The Secondary Solvent Addition Processmentioning
confidence: 99%